Gain of Function for the SCN1A/hNav1.1-L1670W Mutation Responsible for Familial Hemiplegic Migraine - Dhifallah, Sandra; Lancaster, Eric; Merrill, Shana; Leroudier, Nathalie; Mantegazza, Massimo; Cestèle, Sandrine (Frontiers in Molecular Neuroscience, 2018)
The SCN1A gene encodes for the voltage-dependent Nav1.1 Na+ channel, an isoform mainly expressed in GABAergic neurons that is the target of hundreds of epileptogenic mutations. More recently, it has been shown that the SCN1A gene is also the target of mutations responsible for familial hemiplegic migraine (FHM-3) a rare autosomal dominant subtype of migraine with aura. Studies of these mutations indicate that they induce gain of function of the channel. Surprisingly, the mutation L1649Q responsible for pure FHM-3 showed a complete loss of function, but, when partially rescued it induced an overall gain of function because of modification of the gating properties of the mutant channel. Here, we report the characterization of the L1670W SCN1A mutation that has been previously identified in a Chinese family with pure FHM-3, and that we have identified also in a Caucasian American family with pure FHM-3. Notably, one patient in our family had severe neurological deterioration after brain radiation for cancer treatment. Functional analysis of L1670W reveals that the mutation is responsible for folding /trafficking defects and, when they are rescued by incubation at lower temperature or by expression in neurons, modifications of the gating properties lead to an overall gain of function. Therefore, L1670W is the second mutation responsible for FHM-3 with this pathophysiological mechanism, showing that it may be a recurrent mechanism for Nav1.1 hemiplegic migraine mutations.